In memoriam Alasdair Livingstone, 1954–2021 - Facey, William (Proceedings of the Seminar for Arabian Studies, 2022)
His many friends, colleagues and former students were shocked and grieved to learn of the sudden death in January, from Covid, of the Assyriologist Alasdair Livingstone. A man of warmth, humour, and eclectic erudition, he inspired generations of students at Birmingham University, where he had taught since 1993 until his retirement in 2017. His dedication to the history of the ancient Middle East was all the more remarkable for combining a mastery of cuneiform studies with a familiarity not only with the scripts and languages of ancient Arabia but also with Arabic in both classical and colloquial forms.